LABOR PRODUCTIVITY GROWTH IN THE EU - GAP AMONG THE MEMBER STATES - Stangaciu, Ancuta (Studies and Scientific Researches. Economics Edition, 2017)
In our endeavor to analyze the labor productivity gap among the member states for the period 2000-2015, we started by assessing, on territorial profile, the indicators pertaining to descriptive statistics and the results of the hierarchical cluster analysis. In order to highlight the convergence of labor productivity growth in the EU28, two regression equations have been drawn up, in which the independent variable was labor productivity in 2000, and the dependent variable was the dynamics of the indicator registered in 2015 compared to 2000, respectively its value at the end of the period subjected to the analysis.